Dukungan Keluarga Berhubungan dengan Asupan Energi Anak Retardasi Mental di SLB Negeri 01 Kabupaten Bantul - Bunga Astria Paramashanti; Arief Rakhman; Lia Endriyani (Alma Ata University Press, 2016)
People with Mental Retardation mostly do not get proper support and care from their families, it is likely that families keep distance from public due to embarrasement of having a family member with such condition. Family support in this term plays an essential role in terms of child growth, which may be influential to physical aspect, self-care, communication, socialization, mentality, and emotion. Children will be malnourished if the nutrition necessary to support growth process is not fulfilled appropriately. The purpose of this research is to identify the relation between family support and energy intake in children with mental retardation in SLB N 01 of Bantul, Yogyakarta. This research was a quantitative research with cross sectional design. Population in this research was all children with mental retardation since the age of elementary school until senior high school. Samples in this research were 66 subjects. Data collection used questionnaires and systematic random sampling. Data was analyzed by using Kendal Tau statistical test. Results found that respondents who had good family support and sufficient energy intake were 27 subjects (40.9%), subjects who had fair family support and sufficient energy intake were 13 subjects (19.7%), subjects with sufficient family support and insufficient energy intake were 10 subjects (15,2%). According to Kendal Tau analysis, it was showed that p-value was 0.001 (p<0.05) which described that there was a significant relation betweeen family support and energy intake in children with mental retardation in SLB N 01 of Bantul, Yogyakarta. Therefore, it is essential to provide motivation and education for parents with mentally retarded children, especially on child food intake.